Production, Processing and Application of Research Reactor Produced Fluorine-18 Radiopharmaceutical - Dunson, George L.; Crofford, William C.; Hosain, Fazle; Jones, Alfred E.; Mellor, Marilyn K. (Nuklearmedizin - NuclearMedicine, 1971)
Fluorine-18 was produced in a low power research reactor from enriched lithium-6 carbonate. The radiopharmaceutical quality 18F was produced within fifteen minutes by separating it from tritium and lithium. Evaluation of radiochemical purity and biological assay showed the product could be administered orally or parenterally. Oral administration to fasting patients resulted in high quality bone scans.